2019
DOI: 10.3390/w11112303
|View full text |Cite
|
Sign up to set email alerts
|

The Expected Shoreline Effect of a Marine Energy Farm Operating Close to Sardinia Island

Abstract: Coastal areas are defined by numerous opportunities and threats. Among them we can mention emerging renewable projects and on the other hand coastal erosion. In the present work, the impact of a generic wind–wave farm on the nearshore waves and currents in the vicinity of the Porto Ferro inlet (northwest Sardinia) was assessed. Using a reanalysis wave dataset that covers a 40-year interval (1979–2018), the most relevant wave characteristics in the target area were identified. These can reach during winter a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…One indicator for the stability of a beach sector is represented by the dominant breaking mechanisms of the waves that for the Giglio Island are divided between spilling, plunging, and surging [46]. It is considered that a spilling wave is the only one capable to bring sediments from the offshore area, and therefore it will be ideal to obtain this type of wave throughout the use of a marine energy farm [47]. In Figure 11 is presented such an evaluation, considering only the nearshore lines L2, L4, and L5.…”
Section: Additional Wave Parametersmentioning
confidence: 99%
“…One indicator for the stability of a beach sector is represented by the dominant breaking mechanisms of the waves that for the Giglio Island are divided between spilling, plunging, and surging [46]. It is considered that a spilling wave is the only one capable to bring sediments from the offshore area, and therefore it will be ideal to obtain this type of wave throughout the use of a marine energy farm [47]. In Figure 11 is presented such an evaluation, considering only the nearshore lines L2, L4, and L5.…”
Section: Additional Wave Parametersmentioning
confidence: 99%
“…This assumption was based on various analyses that were performed on the general characteristics of the wave climates in the areas targeted. See, for example, the results presented in [31][32][33][34]38,48]. The case studies presented in this work were processed by using the ISSM (Interface for SWAN and Surf Models) modelling tool that combines a wave model with a surf model [49][50][51].…”
Section: Target Areasmentioning
confidence: 99%
“…The variations of the wave conditions in the presence of the marine energy farm will be assessed in the geographical space through spatial maps, while a deeper analysis of these fluctuations will be highlighted along the L-reference lines, or by the analysis performed in some offshore and nearshore points (O-points or NP-points). [33,34,38,48].…”
Section: Target Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…This study focused in assessing how changing the wave transmission coefficient and the distance of the WEC farm to the coast affects the wave height reduction in the lee of the WEC farm, obtaining wave height reductions in the range of 25% to 50%. The authors extended this study to the Mediterranean sea in Reference [7], modelling different WEC farms of up to 24 WECs. In this study, they found wave height reductions varying from 2% to 41%, which in some cases were affecting the wave breaking type.…”
Section: Introductionmentioning
confidence: 99%